A Strategy to Treat COVID‐19 Disease With Targeted Delivery of Inhalable Liposomal Hydroxychloroquine: A Preclinical Pharmacokinetic Study - Tai, Tien‐Tzu; Wu, Tzung‐Ju; Wu, Huey‐Dong; Tsai, Yi‐Chen; Wang, Hui‐Ting; Wang, An‐Min; Shih, Sheue‐Fang; Chen, Yee‐Chun (Clinical and translational science, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a newly identified pathogen causing the coronavirus disease 2019 (COVID‐19) pandemic. Hydroxychloroquine (HCQ), an antimalarial and anti‐inflammatory drug, has been shown to inhibit SARS‐CoV‐2 infection in vitro and tested in clinical studies. However, achievement of lung concentrations predicted to have in vivo antiviral efficacy might not be possible with the currently proposed oral dosing regimens. Further, high cumulative doses of HCQ raise concerns of systemic toxicity, including cardiotoxicity. Here, we describe a preclinical study to investigate the pharmacokinetics (PKs) of a novel formulation of liposomal HCQ administered by intratracheal (IT) instillation in Sprague‐Dawley rats. Compared with unformulated HCQ administered intravenously, liposomal HCQ showed higher (~ 30‐fold) lung exposure, longer (~ 2.5‐fold) half‐life in lungs, but lower blood exposure with ~ 20% of peak plasma concentration (Cmax) and 74% of area under the curve from 0 to 72 hours (AUC0–72) and lower heart exposure with 23% of Cmax and 58% of AUC0–24 (normalized for dose). Similar results were observed relative to IT administration of unformulated HCQ. These PKs result in an animal model that demonstrated the proof of concept that inhalable liposomal HCQ may provide clinical benefit and serve as a potential treatment for COVID‐19.